Kajian Investasi Petani Lahan Pasang Surut di Kabupaten Banjar - Emy Rahmawati (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The objectives of the research are to find out the sources of farmer’s income, investment capital needed by the farmer, to analyze factors influencing the farmer’s investment, and to identify problems faced by tidal land farmers in investing. The descriptive analysis indicated that the greatest contribution of the income of non surjan tidal land farmers and the irrigated land farmers was derived from the rice farming while the tidal land farmers with surjan system were originated from orange. The biggest capital of farming investment was the investment for land purchase, livestock, and farm equipment. It could be indicated from regression analysis that the off-farm income, the acreage, and the education level significantly and positively influenced the investment while the number of working family members and the age of farmers had negative influence. There were no significant differences in investment spending between farmers in tidal land villages and irrigated villages whereas there were significant differences between the farmers in surjan and non-surjan system villages where the farmers in the village with surjan system had smaller investment in farm equipment but bigger one in education, noneducation, and total investment than the farmers in the village with non-surjan system. The limited wage labor, skill limitation, the lack of awareness and the environmental factors were the constraints in the investment practiced by farmers in tidal land. The limited capital was the separate obstacle to the small farmers.